2007
DOI: 10.1167/iovs.06-0954
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Intraocular Drug Delivery by Periocular Injections Using Ocular Fluorophotometry

Abstract: NaF reaches the choroid/retina by transscleral diffusion from the periocular depot. The orbital and conjunctival vasculature and lymphatics have a larger role in NaF clearance than does the choroid. NaF diffuses into the vitreous from the choroid and the anterior segment; the periocular depot location determines the predominant diffusion pathway. The duration of high NaF levels in the choroid/retina or the anterior segment determines vitreous NaF levels. PST is the best periocular route for vitreous NaF delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 18 publications
2
64
0
Order By: Relevance
“…A previous study reported that higher intraocular concentrations in the anterior segment of the eye were achieved by this route in comparison to the systemic route (Ghate et al, 2007). It may be admitted, that due to the interval adopted between each aqueoucentesis, desirable indexes of the drug could not be able to reach the anterior chamber, like reported by Galera (2002).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…A previous study reported that higher intraocular concentrations in the anterior segment of the eye were achieved by this route in comparison to the systemic route (Ghate et al, 2007). It may be admitted, that due to the interval adopted between each aqueoucentesis, desirable indexes of the drug could not be able to reach the anterior chamber, like reported by Galera (2002).…”
mentioning
confidence: 72%
“…Recently, Ghate et al (2007) reported that increased volumes of sodium fluorescein delivered to the eye by different periocular routes have a larger role in transcleral drug delivering than this concentration itself; thus, the inefficacy of carprofen in blocking the anterior uveal tract inflammation may also be explained by the low dose used in this study (0.2mL). The high viscosity of the agent hindered that higher volumes could be injected into the subconjunctival space.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Compared with human eyes, the rabbit eye has thinner scleral thickness (2/3 thickness), smaller vitreous volume, and higher choroidal flow rates. 1,17,18 However, the scleral permeability, and the anatomy and physiology of the lymphatic system, is similar. 19,20 Ultimately, how these differences would effect the pharmacokinetics of trans-sclerally delivered drugs in human eyes is difficult to predict, but nevertheless, the rabbit model is an established, useful model for estimating trans-scleral drug pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the permeation of labeled drug through donor sclera can be measured accurately via fluorometry, labeled drug concentration in the vitreous can be measured via ocular fluorophotometry, and the presence of drug within the sclera can be detected with fluorescein microscopy. 1,2 Even though NaF has proven useful in drug-delivery research, it is limited by photobleaching 3 and pH sensitivity, 4 and thus, more stable, alternative fluorescent agents would be beneficial.…”
Section: Introductionmentioning
confidence: 99%